Validity and Reliability of Spiritual Competency Instruments of Police Members Using Confirmatory Factor Analysis - Firdaos, Rijal; Sanur Tarihoran, Wahdan; Aspandi, Aspandi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2025)
This study aims to measure the spiritual competency construct of members of the Indonesian National Police. The population in this study comprises 323 police members, including 267 male and 56 female officers. The method in this study uses a Likert-scale survey. The study's results empirically indicate that the 37 items of the instrument measuring spiritual competence are distributed across three dimensions. The results of the construct validity using factor analysis indicate that a number of items have been successfully estimated as seven indicators, with factor loadings>0.50. Of the 37 existing items, based on the MSA number, all have been above 0.5. As for the second stage, the assessment based on the loading factor, there were 11 items that fell because they did not meet the requirements. The other 26 items were declared valid based on the consolidation analysis, with factor loadings>0.50.